2015
DOI: 10.1097/shk.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

Delayed but not Early Treatment with DNase Reduces Organ Damage and Improves Outcome in a Murine Model of Sepsis

Abstract: Sepsis is characterized by systemic activation of coagulation and inflammation in response to microbial infection. Although cell-free DNA (cfDNA) released from activated neutrophils has antimicrobial properties, it may also exert harmful effects by activating coagulation and inflammation. The authors aimed to determine whether deoxyribonuclease (DNase) administration reduces cfDNA levels, attenuates coagulation and inflammation, suppresses organ damage, and improves outcome in a cecal ligation and puncture (CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 33 publications
6
86
0
2
Order By: Relevance
“…In contrast, we have shown that delayed administration of DNase in mice subjected to cecal ligation and puncture is beneficial, resulting in a reduction of CFDNA-mediated coagulation and a reduction in bacterial dissemination presumably because the bulk of the microbes are already disarmed by NETs. 60 The findings of this study suggest that the CFDNA component of NETs not only traps circulating pathogens, but may also work in tandem with fibrin to prevent systemic dissemination of microbes by limiting plasmin-mediated fibrin degradation. Thus, understanding the balance between the beneficial and deleterious effects of a hypofibrinolytic state in sepsis is critical to the development of therapeutic strategies.…”
mentioning
confidence: 73%
“…In contrast, we have shown that delayed administration of DNase in mice subjected to cecal ligation and puncture is beneficial, resulting in a reduction of CFDNA-mediated coagulation and a reduction in bacterial dissemination presumably because the bulk of the microbes are already disarmed by NETs. 60 The findings of this study suggest that the CFDNA component of NETs not only traps circulating pathogens, but may also work in tandem with fibrin to prevent systemic dissemination of microbes by limiting plasmin-mediated fibrin degradation. Thus, understanding the balance between the beneficial and deleterious effects of a hypofibrinolytic state in sepsis is critical to the development of therapeutic strategies.…”
mentioning
confidence: 73%
“…Neutrophils have further previously been suggested to be the major source of circulating levels of both dsDNA and nucleosomes [10, 24]. As NETs probably hold prothrombotic properties like platelet activation [18], coagulation activation by factor XII and tissue factor, tissue factor pathway inhibitor (TFPI) suppression [19, 20] and inhibition of fibrinolysis [21], a role in coronary thrombosis would be plausible. As the present sample size was limited and the infarcts were relatively small, possible linkages between the assessed markers of NETs and coronary thrombosis need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…NETs are also suggested to be present in coronary thrombi [8, 9], in mural atherosclerotic plaques [16, 17], and in stable angina pectoris (AP) where they further seem to serve as a predictor of coronary artery severity and risk of new coronary events [10]. By the seemingly wide-ranging prothrombotic properties like platelet entrapment and activation [18], activation of the coagulation system [19, 20], and inhibition of fibrinolysis [21], NETs are potentially important players in the pathogenesis of atherothrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Increased NET formation and accumulation may occur before, or close to the disease onset without proper clearance mechanisms, as shown for traumatized or septic adults. 39,40 NET formation in the intestine with released DNA and neutrophil-derived calprotectin has been shown to be associated with NEC, 26 but it was not clear if circulating NETs may play a role. In the present study, elevated circulating cfDNA levels 1-6 d before NEC onset in preterm infants suggest that sub-clinical systemic inflammation at an early stage of NEC may stimulate neutrophils to release DNA and antimicrobial proteins in the circulation, which may add further inflammatory insults that could advance NEC progression.…”
Section: Discussionmentioning
confidence: 99%